Pengaruh Kualitas Produk, Harga dan Word of Mouth Terhadap Keputusan Pembelian Konsumen Pada Kegiatan Car Free Day (CFD) Pandaan - Nuzila, Firdausi Fauziyatin; Hidayati, Nur; Novianto, Abdullah Syakur (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to determine the influence of product quality, price, and word of mouth on consumer purchasing decisions during the Car Free Day event in Pandaan. This type of research uses a quantitative approach with descriptive analysis methods. The sampling technique used accidental sampling. The required respondents 85 with the sample criteria for this study being consumers who had purchased products from MSME traders during the car free day in Pandaan. The analysis method used was multiple linier regression. The F-test results indicate that product quality, price, and word of mouth simultaneously influence purchasing decisions. Product quality has a positive and significant effect on purchasing decisions, price has a positive and significant effect on purchasing decisions, and word of mouth has a positive and significant effect on purchasing decisions. Keywords: Product Quality, Price, Word Of Mouth